Actants in the ‘Object Donor List’: - Kusumita Datta (Sanglap: Journal of Literary and Cultural Inquiry, 2021)
An official process of the naming of ‘martyr’ by the National Freedom Fighter Council or inclusion of a person’s name in the list for martyr awards in Bangladesh depends on or at times is supplemented by enlistment in the ‘Object Donor List’. Here, martyr ephemera are enlisted and updated on the official website of the Liberation War Museum in the capital city of Dhaka in Bangladesh. Ephemera are minor, transient objects of everyday life. An exploration of martyr ephemera as concretely studied actants thereby recognizes the sacrifices of common people rooted in a democratic object ontology. This study rethinks the post-human identity of the dead martyr and the post-death identity of the more-than-human martyr through the human, non-human and interjectional materialities of actants. Not expected to exist beyond the martyr’s lived moment in history, martyr ephemera will be specifically used to challenge the premises of materialities of the post-human and the post-death. Donated by families and relatives of martyrs coming from various regions, or officials associated with the martyrdom process of an individual, containing personal belongings, paper documents, photographs, print media, they evoke new narratives of an archive in the framework of posthuman museum practices. These narratives are structured around the social intra-active agency, the political affect of the body-politic, spatial actants of the everyday cutting across classes and the space of the museum and the ongoing intra-active agency of actants as ephemera. New materialist modes and mediums will enable a rethinking of the human, the non-human, the more-than-human and its intra-active agencies to assess how they comprise a people’s narrative of the 1971 Liberation War martyr legacy. These narratives are an attempt to initiate new materialisms into the domain of martyr ephemera studies.